Three diamensional (3-D) virtual human cadaver, anatomage: an effective teaching tool for human anatomy - Narnaware, Yuwaraj; Zhang, Chunyan (My University, 2017)
Anatomy education has always been regarded as an essential requirement in the curriculum of medical and other health related disciplines (Turney, 2007). Although there are multiple reports discussing the indispensable importance of anatomy education, there are still ample debates regarding the use of the most effective anatomy teaching method. In an attempt to explore innovative ways to enhance understanding and/or knowledge of the human body in terms of its structure and function, the present study investigates the use of the most advanced and recent sophisticated technological invention, Anatomage. Here, we determine whether the introduction of the virtual human cadaver in the teaching of human anatomy to nursing students and other health sciences students enhances their knowledge of the human body.
Keywords: anatomy; postsecondary education; nursing